Promiscuity in post‐transcriptional control of gene expression: Drosophila sex‐lethal and its regulatory partnerships. Issue 11 (28th April 2017) - Moschall, Rebecca; Gaik, Monika; Medenbach, Jan
Abstract : The Drosophila RNA‐binding protein Sex‐lethal (Sxl) is a potent post‐transcriptional regulator of gene expression that controls female development. It regulates the expression of key factors involved in sex‐specific differences in morphology, behavior, and dosage compensation. Functional Sxl protein is only expressed in female flies, where it binds to U‐rich RNA motifs present in its target mRNAs to regulate their fate. Sxl is a very versatile regulator that, by shuttling between the nucleus and the cytoplasm, can regulate almost all aspects of post‐transcriptional gene expression including RNA processing, nuclear export, and translation. For these functions, Sxl employs multiple interactions to either antagonize RNA‐processing factors or to recruit various coregulators, thus allowing it to establish a female‐specific gene expression pattern. Here, we summarize the current knowledge about Sxl function and review recent mechanistic and structural studies that further our understanding of how such a seemingly 'simple' RNA‐binding protein can exert this plethora of different functions. Abstract :